Application Of Dramatic Elements In Theatre Performances In The 2023 Sunda Language Drama Festival - Precillia, Monita (Institut Seni Indonesia Padangpanjang, 2024)
The research entitled Application Of Dramatic Elements In Theatre Performances In The 2023 Sunda Language Drama Festival uses qualitative research methods: observation, interviews, documentation, and data analysis. This research discusses how Sunda plays a role in building the dramatic elements of theater performances. The issue of the diminishing existence of regional languages is one of the factors in the formation of the Sunda Language Drama Festival. The Sunda Language Drama Festival does not focus on the application of Sunda dialectics but on the form of performance, so that Sunda only becomes a language in communication. these conditions are certainly not effective if the purpose of the Sunda Language Drama Festival is an effort to maintain Sunda. The phenomenon of shifting language use and forms of regional language preservation is an urgency to study at this time, one example is the Sunda Language Drama Festival. This paper aims to analyze the effect of Sunda dialogue on the dramatic structure of the performance.